Sustained, Low Prevalence of Undiagnosed HIV Among Gay and Bisexual Men in Sydney, Australia Coincident With Increased Testing and Pre-exposure Prophylaxis Use: Results From Repeated, Bio-Behavioral Studies 2014–2018. (1st November 2020) - Keen, Phillip; Lee, Evelyn; Grulich, Andrew E.; Prestage, Garrett; Guy, Rebecca; Stoove[Combining Acute Accent], Mark A.; Bavinton, Benjamin R.; Asselin, Jason; Hammoud, Mohamed A.; Broady, Tim; Duck, Tim; Holt, Martin
Abstract : Background: Gay and bisexual men with undiagnosed HIV contribute disproportionately to HIV transmission in Australia. Methods: In 2014 and 2018, we recruited men at gay venues and events in Sydney. Participants self-completed surveys and provided oral fluid samples for HIV testing. We calculated the prevalence of HIV and undiagnosed infection, and assessed changes in behavior, HIV testing, and the use of pre-exposure prophylaxis. We weighted the samples to adjust for differences in where participants were recruited between rounds. Two-sample tests of proportion were used to compare prevalence estimates and χ 2 tests to assess differences between the samples. Results: In 2014, 944 men were recruited, and 890 men were recruited in 2018. In 2014, the weighted estimate of HIV prevalence was 6.1% [95% confidence intervals (CI): 4.6 to 7.6], of which 13.8% (95% CI: 5.0 to 22.7) was undiagnosed. In 2018, weighted HIV prevalence was 6.4% (95% CI: 4.8 to 8.0), of which 5.3% (95% CI: 0.5 to 11.1) was undiagnosed. Between 2014 and 2018 among all participants, men reporting at least 10 recent casual partners increased from 22.3% to 27.7% ( P = 0.008), condomless anal intercourse with casual partners in the previous 6 months increased from 23.9% to 37.3% ( P < 0.001), and sexually transmitted infection diagnoses in the previous year increased from 14.4% to 27.5% ( P < 0.001). HIV testing and the use of pre-exposure prophylaxis in the previous 6 months increased from 49.6% to 56.3% ( P = 0.004) and 2.0%–21.0% ( P < 0.001), respectively. Conclusions: Repeated, bio-behavioral surveillance suggests the prevalence of undiagnosed HIV remains low in Sydney, despite gay and bisexual men reporting more casual sex partners, condomless sex, and sexually transmitted infections.